1983
DOI: 10.1038/305056a0
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to the acetylcholine receptor by a normally functioning auto-anti-idiotypic mechanism

Abstract: Recently we described a procedure for preparing antibodies to the acetylcholine receptor (AChR) based on immunoglobulin idiotypes and on the hypothesis that, regardless of functional differences, macromolecules of the same specificity will show structural homologies in their binding sites. Antibodies were prepared in rabbits to a structurally constrained agonist of AChR, trans-3,3'-bis[alpha-(trimethylammonio)methyl]azobenzene bromide (BisQ). These antibodies mimicked the binding specificity of AChR in its act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The strategy for the preparation of monoclonal anti-IdAb follows Cleveland et al (19). Eight-week-old female'BALB/c mice were immunized i.p.…”
Section: Methodsmentioning
confidence: 99%
“…The strategy for the preparation of monoclonal anti-IdAb follows Cleveland et al (19). Eight-week-old female'BALB/c mice were immunized i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental evidence for auto-anti-Ids is sparse, but most studies have depended on serological methods (61). Very recent studies using mono clonal antibody technology suggest that auto-anti-Ids are readily detectable (62)(63)(64)(65)(66) Since the mechanism of symmetrical stimulation is antibody dependent, it is necessary to consider the possible breaking of symmetry by S-antigens in cases where Id or anti-Id has an anti-S specificity. It will be recalled that the breaking of symmetry by S-antigens is a crucial factor in the an tagonism of Id-anti-Id pairs.…”
Section: Mechanistic Basis Of the Principle Of Symmetrical Stimulationmentioning
confidence: 99%
“…According to the anti-idiotypic network theory of Jerne (32), injection of an antigen elicits antibodies to the antigen and, in addition, anti-idiotypic antibodies directed at the antigen-combining site (Fab hypervariable region) of the antigen-specific antibodies. It has been shown that production of antigen-specific antibodies against a ligand of a receptor results in anti-idiotypic antibodies that bind to the receptor itself (24,33,34). For example, immunization with insulin results in the production not only of antibodies to insulin (idiotypes) but also of antibodies that recognize the insulin receptor (anti-idiotypes) which are produced against the anti-insulin antibodies (35,36).…”
mentioning
confidence: 99%